WEB-BASED INFORMATION TECHNOLOGY FOR CLASSIFYING AND INTERPRETING EARLY PNEUMONIA BASED ON FINE-TUNED CONVOLUTIONAL NEURAL NETWORK (Computer systems and information technologies, 2021)
There have been rapid development and application of computer methods and information systems in digital medical diagnosis in recent years. However, although computer methods of medical imaging have proven helpful in diagnosing lung disease, for detecting early pneumonia on chest X-rays, the problem of cooperation between professional radiologists and specialists in computer science remains urgent. Thus, to address this issue, we propose information technology that medical professionals can employ to detect pneumonia on chest X-rays and interpret the results of the digital diagnosis. The technology is presented as a web-oriented system with an available and intuitive user interface. The information system contains three primary components: a module for disease prediction based on a classification model, a module responsible for hyperparameter tuning of the model, and a module for interpreting the diagnosis results. In combination, these three modules form a feasible tool to facilitate medical research in radiology. Moreover, a web-based system with a local server allows storing personal patient data on the user's computing device, as all calculations are performed locally.
Keywords: information technology; web-system; pneumonia; chest X-ray; convolutional neural network; hyperparameter fine-tuning; class activation maps